PENGARUH SELF ACTUALIZATION, KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN PADANG LAWAS - Fakhri Fauza; Paimin .; Syaiful Azmi A. Mingka; Taufiqurrohman . (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The purpose of this research was to determine and analyze the influence of organizational characteristics, organizational support and job satisfaction on Self Actualization, Job Satisfaction and International Citizenship Behavior (OCB) on the Employees Performance of Sekretariat Daerah Kabupaten Padang Lawas, both partially and simultaneously. The sample in this research were all employees, amounting to 66 people. Determination of the number of samples using a saturated sample (census). The analysis technique used is descriptive analysis method and multiple linear regression analysis with SPSS 20.00 for windows. The results showed that self actualization had a positive and significant effect on the employees performance of Sekretariat Daerah Kabupaten Padang Lawas; job satisfaction has a positive and significant effect on the employees performance of Sekretariat Daerah Kabupaten Padang Lawas; organizational citicenship behavior has not a significant positive effect on the employees performance of employees of Sekretariat Daerah Kabupaten Padang Lawas; and self actualization, job satisfaction and organizational citizenship behavior simultaneously have a positive and significant effect on the employees performance of Sekretariat Daerah Kabupaten Padang Lawas. The employees performance of Sekretariat Daerah Kabupaten Padang Lawas can be influenced by self actualization, job satisfaction and OCB of 46.0%. While the remaining 54.0% can be explained by other factors not examined in this research.